A Remarkably Large Phase‐Transition Effect in a Random Copolymer of Oligo(ethylene glycol) Methyl Ether Methacrylate (OEGMA)500 Induced by the Photochemistry of the 2‐(Hydroxyimino)aldehyde Group. Issue 13 (29th May 2019) - D'Acunzo, Francesca; De Santis, Serena; Masci, Giancarlo; Nardi, Martina; Renzi, Polyssena; Sobolev, Anatoly Petrovich
Abstract: The effect of UV irradiation on the cloud points (CP) of aqueous solutions of a random 1:1 copolymer of oligo(ethylene glycol) methyl ether methacrylate (OEGMA500 ) and a 2‐(hydroxyimino)aldehyde (HIA) functionalized methacrylate is presented. CPs are determined by visible spectroscopy and dynamic light scattering (DLS). 1 H and 13 C NMR experiments are carried out in D2 O and DMSO‐ d6 on the polymer and on an HIA‐functionalized model of the photoresponsive repeat unit. UV‐irradiated solutions exhibit an unprecedented increase of the phase‐separation temperature for an OEGMA photoresponsive copolymer (10–22 °C, depending on concentration and irradiation conditions). Phase separation is reversible with little hysteresis. With both pristine and irradiated polymer solutions, aggregate dimensions are <10 nm (DLS) at room temperature. Aggregates of >100 nm form at the CP and gradually grow as temperature increases, whereas the light‐induced processes of the repeat unit model in DMSO‐ d6 are well identified (e.g., oxime E / Z isomerization and Norrish‐Yang cyclization of the aldehyde moiety), it is not straightforward to extrapolate such behavior to the polymeric solution in water. The remarkably large phototriggered thermal effect in the present work motivates further investigations on the solvent‐dependent photochemistry of HIA as a promising functional group for the synthesis of multi‐stimuli responsive materials. Abstract : Aqueous solutions of a 1:1 random copolymer of oligo(ethylene glycol) methyl ether methacrylate (OEGMA)500 with a methacrylate bearing the 2‐(hydroxyimino)aldehyde (HIA) functional group exhibit a remarkably large upward shift in cloud point upon photostimulation at 350 nm. The rich photochemistry of the HIA group, which may entail changes in dipole moments and hydrogen bonding patterns or trigger dark chemical reactions, is amenable for this effect.